Comprehensive serial molecular profiling of an "N of 1" exceptional non-responder with metastatic prostate cancer progressing to small cell carcinoma on treatment. Issue 1 (December 2015) - Kadakia, Kunal; Tomlins, Scott; Sanghvi, Saagar; Cani, Andi; Omata, Kei; Hovelson, Daniel; Liu, Chia-Jen; Cooney, Kathleen
Abstract Importance Small cell carcinoma/neuroendocrine prostate cancer (NePC) is a lethal, poorly understood prostate cancer (PCa) subtype. Controversy exists about the origin of NePC in this setting. Objective To molecularly profile archived biopsy specimens from a case of early-onset PCa that rapidly progressed to NePC to identify drivers of the aggressive course and mechanisms of NePC origin and progression. Design, setting, and participants A 47-year-old patient presented with metastatic prostatic adenocarcinoma (Gleason score 9). After a 6-month response to androgen deprivation therapy, the patient developed jaundice and liver biopsy revealed exclusively NePC. Targeted next generation sequencing (NGS) from formalin-fixed paraffin-embedded (FFPE)-isolated DNA was performed from the diagnostic prostate biopsy and the liver biopsy at progression. Intervention Androgen deprivation therapy for adenocarcinoma followed by multiagent chemotherapy for NePC. Main outcomes and measures Identification of the mutational landscape in primary adenocarcinoma and NePC liver metastasis. Whether the NePC arose independently or was derived from the primary adenocarcinoma was considered based on mutational profiles. Results A deleterious somaticSMAD4 L535fs variant was present in both prostate and liver specimens; however, aTP53 R282W mutation was exclusively enriched in the liver specimen. Copy number analysis identified concordant, low-level alterations in both specimens, with focalMYCL amplification and homozygousPTEN, RB1, andMAP2K4 losses identified exclusively in the NePC specimen. Integration with published genomic profiles identifiedMYCL as a recurrently amplified in NePC. Conclusions and relevance NGS of routine biopsy samples from an exceptional non-responder identifiedSMAD4 as a driver of the aggressive course and supports derivation of NePC from primary adenocarcinoma (transdifferentiation).